Female fertility preservation: Impact of cancer on ovarian function and oocyte quality. Issue 1 (28th April 2021) - Fabiani, Cristina; Ferrante, Maria Giulia; Meneghini, Caterina; Licata, Emanuele; Paciotti, Gemma; Gallo, Mariagrazia; Schiavi, Michele; Spina, Vincenzo; Guarino, Antonella; Caserta, Donatella; Rago, Rocco
Abstract: Objective: To evaluate the influence of cancer on ovarian response and oocyte quality in controlled ovarian hyperstimulation (COH). Methods: This prospective study conducted at the Physiopathology of Reproduction and Andrology Unit of Sandro Pertini Hospital enrolled 82 cancer patients undergoing controlled ovarian stimulation (COH) cycles for fertility preservation, and age‐ and date‐matched controls undergoing COH for in vitro fertilization for male‐factor infertility from June 2016 to November 2019. The interventions performed were COH, oocyte retrieval, and quality evaluation. Main outcome measures were maximal estradiol levels on the day of human chorionic gonadotropin administration, duration of stimulation, total amount of gonadotropins administered, number of oocytes retrieved, and rates of metaphase 2 oocytes and abnormal oocytes. All data were analyzed using the Statistical Package for the Social Sciences (IBM Corp., Armonk, NY, USA) 22.0. Results: Intergroup comparisons (82 cancer patients and 180 patients in control group) showed a significant difference in ovarian response, especially for a significant higher number of abnormal oocytes in cancer patients ( P < 0.0001). Regression analysis to assess the influence of the neoplastic process, regardless of the type, on ovarian response showed an effect on the main outcome measured due to cancer itself. Conclusion: Cancer influences the ovarian response, particularly the oocyte quality, during COH performed for fertility preservation. Synopsis: This study highlights the influence of cancer on oocyte quality during controlled ovarian hyperstimulation and underlines the significant findings regarding abnormal oocytes in cancer patients.